Effect of modified Traditional Chinese Medicine external application in the treatment of pruritus in patients with chronic cholestatic liver disease (细化中药涂药技术干预慢性胆汁淤积性肝病患者皮肤瘙痒的护理效果评价) - LI Xue (李雪); ZHAO Haiqin (赵海芹); BAI Lirong (白丽荣); LIU Xiaojing (刘晓静) (中西医结合护理)
Objective To observe the effect of modified Traditional Chinese Medicine external application in the treatment of pruritus in patients with chronic cholestatic liver disease, and to improve the quality of Tradition Chinese Medicine nursing of liver diseases. Methods Totally 112 patients with chronic cholestatic liver disease complicated with pruritus were randomly divided into the control group (n=55) and Traditional Chinese Medicine (TCM)group (n=57). According the occurrence time, frequency and influence of skin temperature on itch, the Traditional Chinese Medicine external application method was modified. Modified Traditional Chinese Medicine external application with calamine lotion and Qingre-Lishi-Zhiyang recipe was carried out in the control group and TCM group, respectively. The effect of nursing interventions was measured and compared between two groups. Results The rate of cured and remarkably improved outcome in the TCM group was 80. 70%(46/57) and 40%(22/55)in the control group, with a significant difference(P ＜0. 01). The levels of total bilirubin (TBIL) and Total bile acid (TBA)in the TCM group were lower than those in the control group after intervention (P＜0. 01). A lower pruritus symptom score and shorter duration of itching were found in the TCM group compared with those in the control group (P＜0. 01). Patients in the TCM group had a longer sleep time compared with that in the control group after nursing intervention (P＞0. 05). The lesion symptom score in the TCM group was lower than that in the control group (P＜0. 01). A better improvement of dry skin was observed in the TCM group compared with that in the control group after intervention (P＜0. 01). Conclusion The modified Traditional Chinese Medicine external application with Qingre-Lishi-Zhiyang recipe is effective in the treatment of pruritus in patients with chronic cholestatic liver disease. (目的 观察细化关键技术操作环节的中药涂药疗法干预胆汁淤积性肝病患者皮肤瘙痒症状的效果, 提升中医肝病专科护理质量。方法 选取2021年1月—2022年12月医院收治的慢性胆汁淤积性肝病并发皮肤瘙痒症患者112例为研究对象, 将患者随机分为对照组55例和中药组57例。结合患者皮肤瘙痒症状常出现的时间、频率及温度对其瘙痒程度影响的特点, 对涂药前清洁皮肤水温的设定和涂药时间进行细化研究。在此基础上, 采用中药涂药技术干预两组患者皮肤瘙痒症状, 分别给予对照组炉甘石洗剂和中药组清热利湿止痒方外涂进行干预。对比两组患者护理效果。结果 中药组护理干预愈显率80. 70%(46/57), 高于对照组的40%(22/55), 差异有统计学意义(P＜0. 01)。干预后, 中药组总胆红素(TBIL)和总胆汁酸(TBA)水平低于对照组, 差异有统计学意义(P＜0. 01); 与对照组比较, 中药组瘙痒程度积分降低, 瘙痒持续时间缩短, 差异有统计学意义(P＜0. 01); 中药组患者睡眠时间较对照组延长, 但差异无统计学差异(P＞0. 05); 中药组皮损状态积分低于对照组, 差异有统计学意义(P＜0. 05); 中药组皮肤干燥情况改善优于对照, 差异有统计学意义(P＜0. 01)。结论 临床护理慢性胆汁淤积性肝病患者皮肤瘙痒症状时, 采用细化后的中药涂药技术涂抹清热利湿止痒方效果良好, 有助于提高治疗效果, 改善患者生活质量。)